Difficulties in Learning Arabic Vocabulary (Mufradat) Students of MTs NU Al Falah Jekulo Kudus - Huda, Miftahul (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
This study aims to determine the difficulties of students of Madrasah Tsanawiyah NU al Falah, Jekulo, Kudus, in learning Arabic vocabulary (mufradat) and find out the factors that cause difficulties in learning Arabic vocabulary, as well as an illusion that can be taken to overcome the difficulties of learning Arabic vocabulary. This research is a type of field research using qualitative descriptive methods. Method of collecting data using observation, interviews and documentation. Stages a data analysis with data reduction, data presentation, and data verification. The source of the data comes from class VII students of Madrasah Tsanawiyah NU al Falah, Jekulo, Kudus. The results showed that there are two types of difficulties faced by students in learning Arabic vocabulary (mufradat), namely linguistic (reading and understanding) and non-linguistic factors (educational background and lack of motivation). As for factors the cause is internal factors and external factors. Internal factors are in the form of interests and habits, while external factors, which include educators, families, and communities. Efforts that can be done in overcoming the difficulties faced by students in learning Arabic language vocabulary is by developing learning methods, increasing student interest and motivation in learning and providing attention to children's learning at home. This research can be a reference in order to find out aspect of the difficulties experienced by students as well as efforts that can be made in the process of learning Arabic vocabulary (mufradat) for students at the madrasah level